Development and Simulation of a Hybrid Extrusion Mechanism for Enhanced Surface Quality and Precision in FDM 3D Printing - Ge, Qing; Wang, Yin (Manufacturing Technology Journal, 2024)
FDM forming 3D printers may encounter problems such as rough printing surface and poor accuracy during operation. This study mainly utilizes the complementary advantages of piston extrusion mechanism, sliding vane pump extrusion mechanism, and plunger pump extrusion mechanism to design a parallel combination of three nozzle extrusion mechanism, and conducts simulation experiments to verify its effectiveness based on temperature distribution data comparison. It basically avoids the irregular voids and faults caused by the thermal phase change of materials passing through the nozzle during the printing process.
Keywords: FDM molding; 3D printer; Extrusion mechanism